(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, bioethics is analyzed as a material and spiritual paradigm of society, and it is analyzed that modern bioethics and biotechnology are a multidisciplinary scientific-practical direction in the social development of society today. At the same time, the importance of bioethical personnel in the production process is revealed in the "Society-Social, Group-Human" system. The importance of bioethics and biotechnology in the science-technology and production process appeared on the basis of achievements in biology, in particular (microbiology, genetics, molecular biology, biochemistry, etc.) and engineering sciences. The development of bioethics and biotechnology, in turn, has led to the acceleration of scientific and practical research conducted in several disciplines related to it. In particular, the progress achieved in the issues of synthesizing various physiologically active substances based on microorganisms, creating necessary and economically effective, competitive microbial producers, isolating the necessary products from them, using plant and animal cells and tissues for this purpose confirms. Since biotechnology is multidisciplinary, it is a rather problematic task to reveal all its directions in one article or a specific scientific research work. In the development of bioethical and biotechnological processes, thoughts are given about the history, yesterday, today and tomorrow of this direction. The article tried to clarify the scientific, practical and methodological foundations of modern bioethical and biotechnological processes, in particular, it was explained that the development of production processes of biotechnological processes in the global information space and its main features are the guarantee of the country’s development.